ASSESSING UNDERGRADUATE STUDENTS’ KNOWLEDGE REGARDING APPLICATION OF BIOSTATISTICS IN RESEARCH AT MEDICAL COLLEGE - Singh, Jaya Prasad; Neupane, Sadikshya; Mehta, Raj Kumar; Deo, Gopendra Prasad (Journal of Chitwan Medical College, 2022)
Background: Biostatistics is necessary in every stage of research, beginning from planning to till publication. It helps to gain importance scientifically as well as reliable results, while inappropriate use of statistical method and analysis cause harm to science and humanity. This study was aimed to assess the knowledge regarding biostatistics among different undergraduate students at medical college. Methods: A descriptive cross-sectional study was conducted in Chitwan Medical College among 117 final year students from different stream. Data was collected from 11th May, 2022 to 20st May, 2022. Standardized valid and reliable questionnaire was administered to assess the knowledge regarding application of biostatistics in research. Data was analysed by using software Statistical Package for social Sciences version 25.0. Descriptive statistics was used to calculate frequency, percentage, measure of average, measure of variation and cross tab. Chi-square test and fishers’ exact test was used to test the association between level of knowledge and selected variables. Results: This study included 117 undergraduate students of different health stream aged between 20 to 34 years with average students of Md (Q3-Q1)=23 (25-22) years being the most common age. Majority of the students were female 102 (87.2%). Only few 19 (16.2%) had good knowledge and remaining had fair knowledge regarding application of biostatistics in research. There was strongly evidence of statistically significant difference between level of knowledge and age of the students (p=0.001). Conclusions: This study concluded that only few numbers of undergraduate students had good knowledge and majority had fair knowledge regarding application of biostatistics in research.